2022
DOI: 10.1038/s42003-022-03737-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of natural phenolic compounds in complex at an allosteric site of SARS-CoV-2 papain-like protease

Abstract: SARS-CoV-2 papain-like protease (PLpro) covers multiple functions. Beside the cysteine-protease activity, facilitating cleavage of the viral polypeptide chain, PLpro has the additional and vital function of removing ubiquitin and ISG15 (Interferon-stimulated gene 15) from host-cell proteins to support coronaviruses in evading the host’s innate immune responses. We identified three phenolic compounds bound to PLpro, preventing essential molecular interactions to ISG15 by screening a natural compound library. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…For example, 2,4‐di‐ tert ‐butylphenol was found, which is reported to have strong antioxidant activity 28 . These phenol derivatives are mainly responsible for the antioxidant activity of beverage and are also reported to have anti‐inflammatory and antiviral potential 29 . Eucalyptol, a compound well known to possess antimicrobial properties, was also found in fermented kombucha.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 2,4‐di‐ tert ‐butylphenol was found, which is reported to have strong antioxidant activity 28 . These phenol derivatives are mainly responsible for the antioxidant activity of beverage and are also reported to have anti‐inflammatory and antiviral potential 29 . Eucalyptol, a compound well known to possess antimicrobial properties, was also found in fermented kombucha.…”
Section: Resultsmentioning
confidence: 99%
“…28 These phenol derivatives are mainly responsible for the antioxidant activity of beverage and are also reported to have anti-inflammatory and antiviral potential. 29 Eucalyptol, a compound well known to possess antimicrobial properties, was also found in fermented kombucha. Eucalyptol is a major constituent of essential oils from plants and is also reported to be found in turmeric.…”
Section: Microbiological Characterizationmentioning
confidence: 99%
“…Additionally, with the advancement of instrumentation and the high contrast of reagents, counting can be automated for more precision and less subjectivity in a high-throughput setting [ 163 , 164 , 165 ]. Additionally, other quick and sensitive methods, such as cell-based enzyme-linked immunosorbent assay (ELISA) and quantitative real-time polymerase chain reaction (PCR), are used to determine antiviral activity by measuring the reduction in viral antigen or virus nucleic acid in infected cells in the presence of the test molecule [ 166 , 167 , 168 ]. Similarly, transmission electron microscopy (TEM) can be used to quantify infectious particles and assess the potential antiviral activity of test compounds [ 169 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…As an indispensable resource, phytochemicals ( Beura et al, 2021 ; Kumar et al, 2021 ; Wang and Yang, 2021 ; Wang et al, 2022b ) have demonstrated potential value in countering SARS-CoV-2 infection. Phytochemicals have been used as natural antiviral compounds that can inhibit viral replication or viral entry ( Cheng et al, 2006 ; Lin et al, 2014 ; Chakravarti et al, 2021 ; Srinivasan et al, 2022 ). They are derived from plants, vegetables, fruits, tea, and red wine and are used in traditional medicines.…”
Section: Introductionmentioning
confidence: 99%
“…They are derived from plants, vegetables, fruits, tea, and red wine and are used in traditional medicines. Phytochemicals were shown to inhibit viral replication, RNA synthesis, viral protein synthesis, and block viral attachment to the host cell ( Cheng et al, 2006 ; Lin et al, 2014 ; Chakravarti et al, 2021 ; Srinivasan et al, 2022 ). In the present study, we have investigated the inhibitory effect of several commercially available phytochemicals against the PLpro enzymatic activity assay.…”
Section: Introductionmentioning
confidence: 99%